Peran pustakawan dalam meningkatkan layanan di perpustakaan - Nora Junita Azmar (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2015)
The role of the librarian, growing over time. Now librarians not only serve the circulation of books, but are required to provide information in a rapid, precise, accurate and efficient in terms of time and cost. Librarians are required to develop the competencies that exist within himself to support the creation of quality services in the library. This paper discusses the role of librarians in improving the quality of service at the library